Dynamic Impedance Spectroscopy of Nickel Hexacyanoferrate Thin Films. Issue 21 (20th August 2019) - Erinmwingbovo, Collins; Koster, Dominique; Brogioli, Doriano; La Mantia, Fabio
Abstract: Dynamic multi‐frequency analysis (DMFA) is capable of acquiring high‐quality frequency response of electrochemical systems under non‐stationary conditions in a broad range of frequencies. In this work, we used DMFA to study the kinetics of (de‐)intercalation of univalent cations (Na + and K + ) in thin films of nickel hexacyanoferrate (NiHCF) during cyclic voltammetry. For this system, the classic stationary electrochemical impedance spectroscopy fails due to the instability of the oxidized form of NiHCF. We are showing that such spectra can be fitted with a physical model described by a simple two‐step intercalation mechanism: an adsorption step followed by an insertion step. The extracted kinetic parameters are depending on the state of charge as well on the nature of the inserted cation. Abstract : Watch them evolve : The kinetics of the (de‐)intercalation of univalent cations in NiHCF thin films which is unstable in its oxidized form is studied using dynamic multi‐frequency analysis (DMFA). DMFA allows for the acquisition of time resolved impedance making it suitable for studying unstable or evolving electrochemical systems.